From Retinal Vasculitis to Stroke, from Systemic Findings to Diagnosis, the Necessity of Multidisciplinary Management in Behçet’s Disease: A Case Report - Sayena Jabbehdari; Anthony Oganov; Sami H. Uwaydat (Case Reports in Ophthalmology)
Introduction: Behçet’s disease (BD) is a rare, chronic multisystem disorder characterized by occlusive vasculitis, which can present with a variety of systemic and ocular manifestations. The diagnosis of BD is often challenging, particularly in populations with low prevalence. Retinal vasculitis and stroke can be key indicators, and the early involvement of a multidisciplinary team is essential for accurate diagnosis and management to prevent long-term complications. Case Presentation: A 40-year-old African American female presented with vision changes in her left eye and a history of multiple strokes. Examination revealed retinal ischemia and vasculitis, raising suspicion of an underlying systemic condition. Extensive workup for infectious and inflammatory causes was negative. As her condition progressed, the patient developed genital ulcers, prompting further investigation. A biopsy of the genital ulcer confirmed BD, and a multidisciplinary approach involving ophthalmology, rheumatology, and neurology was initiated. The patient was treated with high-dose corticosteroids, immunosuppressive therapy, and intravitreal corticosteroids, leading to stabilization of her ocular and systemic symptoms. Despite her history of stroke, the collaboration between specialties facilitated better management of her condition and prevention of further complications. Conclusion: It is crucial to include BD as a potential diagnosis in cases of ophthalmic or systemic vasculitis, even in regions and populations with low prevalence. Early referral to a rheumatologist for cases of vasculitis and timely collaboration are essential for accurate diagnosis, prevention of systemic complications, and appropriate management.